Model to measure the readiness of university testing laboratories to fulfill ISO/IEC 17025 requirements (a case study) - Era Febriana Aqidawati; Wahyudi Sutopo; Roni Zakaria (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
Universities are considered as a source of open innovations by producing new technology. The innovations need to be tested in licensed laboratories in order to create certified products if they are to be commercialized to the market. Many universities have established laboratories that provide testing services to society and act as a revenue-generating source. Universitas Sebelas Maret (UNS) owns an accredited center laboratory that provides testing services to external parties. In addition, the university owns other laboratories in several faculties to conduct academic activities and research and yet provide testing services, but have not been accredited. Therefore, the laboratories have the potential to be developed as part of the testing service business to support the incubation process of new technology and provide testing services. In this article, we chose UNS, one of the universities in Indonesia, to develop a framework of readiness level measurement instrument, to evaluate the readiness and to suggest improvements for laboratories to achieve accreditation. A framework of laboratory readiness measurement was developed using integration of management approach and laboratory approach. Descriptive statistics were used to create a radar chart to determine the readiness level. Based on findings and evidence analysis, we proposed improvement planning using ISO 17025 and management concept.
Keywords: 650; assessment framework; innovation; ISO/IEC 17025; readiness level; university testing laboratories